2009
DOI: 10.1152/ajpregu.00253.2009
|View full text |Cite
|
Sign up to set email alerts
|

Is active sweating during heat acclimation required for improvements in peripheral sweat gland function?

Abstract: We investigated whether the eccrine sweat glands must actively produce sweat during heat acclimation if they are to adapt and increase their capacity to sweat. Eight volunteers received intradermal injections of BOTOX, to prevent neural stimulation and sweat production of the sweat glands during heat acclimation, and saline injections as a control in the contralateral forearm. Subjects performed 90 min of moderate-intensity exercise in the heat (35 degrees C, 40% relative humidity) on 10 consecutive days. Heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 27 publications
1
34
1
Order By: Relevance
“…3), likely contributing, alongside reduced skin blood flow (Kenefick et al, 2007) to the reduced mean and peak T sk following STHA, but was not enhanced by a LTHA period of 10 days. Though commonly reported as an adaptation following LTHA (Buono et al, 2009;Chinevere et al, 2008), improved sweat loss after STHA is not unique to our data (Machado-Moreira et al, 2006). Our data show enhanced sudomotor function from STHA in all methods of heat acclimation; as such different work duration or intensity does not induce different sweat rate adaptation.…”
Section: Physiological Mechanisms Of Heat Acclimationsupporting
confidence: 52%
See 1 more Smart Citation
“…3), likely contributing, alongside reduced skin blood flow (Kenefick et al, 2007) to the reduced mean and peak T sk following STHA, but was not enhanced by a LTHA period of 10 days. Though commonly reported as an adaptation following LTHA (Buono et al, 2009;Chinevere et al, 2008), improved sweat loss after STHA is not unique to our data (Machado-Moreira et al, 2006). Our data show enhanced sudomotor function from STHA in all methods of heat acclimation; as such different work duration or intensity does not induce different sweat rate adaptation.…”
Section: Physiological Mechanisms Of Heat Acclimationsupporting
confidence: 52%
“…This adaptation is facilitated by an earlier onset of sweating (Shido et al, 1999). Heat acclimation is also known to induce peripheral changes at the sweat gland to sweat response during exercise-heat stress (Buono et al, 2009;Fox et al, 1964;. Increased cholinergic sensitivity of the eccrine sweat gland or increased glandular hypertrophy is induced by heat acclimation (Sato and Sato, 1983).…”
Section: Physiological Mechanisms Of Heat Acclimationmentioning
confidence: 99%
“…Yet, rectal temperature is negatively correlated to distance covered in intermittent running (Morris, Nevill, Lakomy, Nicholas, & Williams, 1998;Morris, Nevill, & Williams, 2000) and heat strain is negatively correlated to peak power output of 40 min of intermittent sprint cycling (Castle et al, 2006;Maxwell et al, 2008). Therefore, heat acclimation may weaken the negative relationship between heat strain and peak power output and appears to help, in part, by lowering core temperature during exercise by up to 0.48C (Buono, Heaney, & Canine, 1998;Buono, Numan, Claros, Brodine, & Kolkhorst, 2009;Sunderland et al, 2008).…”
mentioning
confidence: 99%
“…post-junctional) components. Post-junctional sudomotor adaptations proposed to contribute to an improved thermal tolerance, include increased post-junctional sensitivity of the sweat glands to cholinergic agonists 17,23,26 , increased number of active sweat glands 27 , an increased efficiency of sweat evaporation 36 , sweat gland hypertrophy 23,29 and/or an increased output of sweat per active gland 2830 .…”
Section: Discussionmentioning
confidence: 99%
“…post-junctional) cutaneous and sudomotor adaptations. In particular, a number of studies have shown that the post-junctional sensitivity of the sweat glands and cutaneous vasculature is increased in uninjured subjects following various heat acclimation regimens 17,23,26-31 . That said, nothing is known about the effects of heat acclimation on post-junctional sensitivity of the sweat glands and cutaneous vasculature in the non-injured, non-donor skin of burn survivors.…”
Section: Introductionmentioning
confidence: 99%